INNOVATIVE POTENTIAL OF RUSSIAN UNIVERSITIES: IMPLEMENTATION STRATEGY, RESEARCH METHODS, DEVELOPMENT FACTORS - Modestovich , Arthur; Vladimirovna , Natalia (Revista Inclusiones, 2020)
The article discusses the various aspects of the formation, functioning and development of Russian universities as innovation centers and suggests ways for their further development. The purpose of the article is to identify and analyse the innovative potential of Russian universities, to uncover socio-economic, institutional, organizational and managerial issues of functioning and justify the ways, methods and tools for their development.The research methodology is based on a systematic approach and includes the combined use of the following research methods: justification of ways, methods and tools for their development, the identification and analysis of factors that influence the external environment on the development strategy of universities, a method for assessing and analyzing factors, processes and phenomena that influence the development of universities as innovation centers, methodological methods for determining and analyzing the strengths, neutral and weaknesses of university innovation development. The main results of the research.